Day 2 Thu, June 25, 2020 2020
DOI: 10.2118/200692-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of EOR Polymers on Scale Inhibitor Adsorption

Abstract: With the current trend for application of Enhanced Oil Recovery (EOR) technologies, there has been much research into the possible upsets to production, from the nature of the produced fluids to changes in the scaling regime. One key question that is yet to be addressed is the influence of EOR chemicals, such as hydrolysed polyacrylamide (HPAM), on scale inhibitor (SI) squeeze lifetime. Squeeze lifetime is defined by the adsorption of the inhibitor onto the reservoir rock, hence any chemical that interacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[ 43 ] In a different study, using hydrolyzed polyacrylamide (HPAM) as the EOR chemicals resulted in a decrease in SI adsorption at both neutral and low pH. [ 42 ] Another study demonstrated that using nanomaterials like CNT and GO in a brine that contains calcium ions can improve the SI adsorption more than DW, but the SI concentration reduction at their ideal experiment (83%) is lower than the optimal condition of this study (93%). [ 44 ] As a result, the ideal scenario for improving scale inhibitor adsorption is to eliminate monovalent cations from SW that may block the adsorbent's surface active sites and keep the divalent cations (both Mg 2+ and Ca 2+ ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…[ 43 ] In a different study, using hydrolyzed polyacrylamide (HPAM) as the EOR chemicals resulted in a decrease in SI adsorption at both neutral and low pH. [ 42 ] Another study demonstrated that using nanomaterials like CNT and GO in a brine that contains calcium ions can improve the SI adsorption more than DW, but the SI concentration reduction at their ideal experiment (83%) is lower than the optimal condition of this study (93%). [ 44 ] As a result, the ideal scenario for improving scale inhibitor adsorption is to eliminate monovalent cations from SW that may block the adsorbent's surface active sites and keep the divalent cations (both Mg 2+ and Ca 2+ ).…”
Section: Resultsmentioning
confidence: 86%
“…-Gypsum nucleation inhibition in the presence of HEDP and PBTC using dynamic light scattering Popov et al [41] DETPMP Seawater À30 μg/g -HPAM Investigating the effect of HPAM and lowering pH on DETPMP adsorption Beteta et al [42] PVS Synthetic brines 22% increase -PEC nanoparticle Increasing the lifetime of PVS in sandstone rock by adding PEC Veisi et al [43] EDTA CaCl Ghorbani et al [45] HEDP PBTC other organic and inorganic substances are among the impurities that are found in oil and gas when they are taken from the ground. These impurities have the potential to precipitate, which can lead to equipment inefficiency, pipeline obstructions, and other operational issues.…”
Section: Introductionmentioning
confidence: 99%